Interleukin-32 positive immune and resident cells in kidney samples from lupus patients: a pilot study - Truglia, Simona; Ciccia, Francesco; Mancuso, Silvia; Capozzi, Antonella; Rizzo, Aroldo; Spinelli, Francesca Romana; Ceccarelli, Fulvia; Colasanti, Tania; Garufi, Cristina; Miranda, Francesca; Sorice, Maurizio; Alessandri, Cristiano; et al. (Frontiers in Immunology, 2025)
IntroductionLupus nephritis (LN), caused by immune complexes produced in situ or deposited from the bloodstream, is one of the most severe features of Systemic Lupus Erythematosus (SLE) leading to an increased morbidity and mortality. Toll like receptors (TLRs), such as TLR3, TLR7 and TLR9, may play a key role in its pathogenesis. Interleukin-32 (IL-32), a cytokine involved in both innate and adaptive immune responses, has been widely considered in autoimmune-inflammatory rheumatic diseases. This study aims to evaluate the IL-32 role in LN, also investigating the effect of LN patients IgG (LN-IgG) on IL-32 production via TLR3.MethodsIn LN patients, IL-32 was detected in sera samples by ELISA KIT and in kidney tissue by immunohistochemistry. HEK293/T3 cells were incubated with LN-IgG and analyzed for TBK1, phospho-p65 NF-κB and IL-32 by Western blot.ResultsWe demonstrated IL-32 presence in LN patients compared to SLE patients without renal involvement, observing a direct correlation between IL-32 serum levels and disease duration (p=0.02; r 0.2978). Moreover, IL-32 was strongly expressed in renal samples of LN patients. Phosphorylation of TBK1 resulting in NF-κB activation and IL-32 increase was observed in HEK293/T3 cells following LN-IgG treatment, TLR3 inhibitor using induced a significant reduction in the expression of these molecules.DiscussionThese results showed that IL-32 is up-regulated in the kidney of LN patients suggesting that in renal tissue IL-32 expression could be induced through TLR3 activation by the LN patients’ antibodies. This study may indicate a possible role for IL-32 in the pathogenesis of LN.